Adrenergic receptor signaling regulates the CD40-receptor mediated anti-tumor immunity - Singh, Akansha; Ranjan, Ashish (Frontiers in Immunology, 2023)
Introduction Anti-CD40 agonistic antibody (αCD40), an activator of dendritic cells (DC) can enhance antigen presentation and activate cytotoxic T-cells against poorly immunogenic tumors. However, cancer immunotherapy trials also suggest that αCD40 is only moderately effective in patients, falling short of achieving clinical success. Identifying factors that decrease αCD40 immune-stimulating effects can aid the translation of this agent to clinical reality. Method/Results Here, we reveal that β-adrenergic signaling on DCs directly interferes with αCD40 efficacy in immunologically cold head and neck tumor model. We discovered that β-2 adrenergic receptor (β2AR) activation rewires CD40 signaling in DCs by directly inhibiting the phosphorylation of IκBα and indirectly by upregulating levels of phosphorylated-cAMP response element-binding protein (pCREB). Importantly, the addition of propranolol, a pan β-Blocker reprograms the CD40 pathways, inducing superior tumor regressions, increased infiltration of cytotoxic T-cells, and a reduced burden of regulatory T-cells in tumors compared to monotherapy. Conclusion Our study highlights an important mechanistic link between stress-induced β2AR signaling and reduced αCD40 efficacy in cold tumors, providing a new combinatorial approach to improve clinical outcomes in patients.